2016
DOI: 10.1002/mnfr.201500790
|View full text |Cite
|
Sign up to set email alerts
|

Phenethyl isothiocyanate and indole‐3‐carbinol from cruciferous vegetables, but not furanocoumarins from apiaceous vegetables, reduced PhIP‐induced DNA adducts in Wistar rats

Abstract: Effects of phytochemicals on metabolic outcomes and markers of carcinogenesis might differ from fresh vegetables, thus limiting the inferences that one can draw from the effects of purified phytochemicals on the health benefits of the vegetables from which they derive.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 44 publications
1
14
0
Order By: Relevance
“…This lack of effect in the fresh CRU group could be because PEITC and I3C levels fed in the phytochemical diet were matched to the total glucosinolate content in our fresh cruciferous feeding due to the variety of glucosinolates in the vegetables with potential bioactivity, yet lack commercially available standards for individual measurement as previously discussed. 7 Thus, these two specific components were higher than in our fresh cruciferous feeding, which would have contained a number of different glucosinolates in addition to the parent compounds of PEITC and I3C. Possibly, other factors might have influenced this difference, such as bioavailability or incomplete hydrolysis of parent glucosinolates.…”
mentioning
confidence: 72%
See 3 more Smart Citations
“…This lack of effect in the fresh CRU group could be because PEITC and I3C levels fed in the phytochemical diet were matched to the total glucosinolate content in our fresh cruciferous feeding due to the variety of glucosinolates in the vegetables with potential bioactivity, yet lack commercially available standards for individual measurement as previously discussed. 7 Thus, these two specific components were higher than in our fresh cruciferous feeding, which would have contained a number of different glucosinolates in addition to the parent compounds of PEITC and I3C. Possibly, other factors might have influenced this difference, such as bioavailability or incomplete hydrolysis of parent glucosinolates.…”
mentioning
confidence: 72%
“…6 We also demonstrated that purified phytochemicals from cruciferous vegetables decreased PhIP-DNA adducts in rat colon, but with less effect from their whole vegetable source. 7 However, there is no study that examined the effects of combined intake of two different vegetable families or their phytochemicals on prostate and pancreas PhIP-DNA adducts. Hence, we exam-ined here whether feeding the aforementioned would result in similar effects in rat prostate and pancreas as seen in colon.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, these vegetables induce acute oxidative stress through the inhibition of P38 MAPK, which inhibits Nrf2-Keap 1 dissociation (Table 1) [164]. Cruciferous vegetables guard against colorectal cancer through several mechanisms: (i) the modulation of detoxification enzymes (Figure 2), (ii) the induction of cellular apoptosis, and (iii) the controlling of cancer cellular growth through cell cycle arrest [165][166][167]. A meta-analysis study has shown that cruciferous vegetables significantly reduce the risk of gastric and colorectal cancer by 19% and 8%, respectively [168].…”
Section: Sulforaphanementioning
confidence: 99%